Propuesta de mejora al sistema de almacenamiento e inventarios del depósito Merca Express - Plata Alonso, Geraldine; Martínez Duarte, Luis Enrique (Universidad Antonio Nariño, 2022)
At present, competition requires business owners to seek new ways to develop their business idea and have better economic stability, thinking of the above, they must make decisions focused on reducing costs, with better quality and improving delivery times.